Polarizing Plate
By using a thermoplastic resin film with low water absorption rate in the polarizing plate and controlling the shrinkage force of the polarizing plate, the problem of light leakage in the polarizing plate after high temperature is solved, and the effect of reducing light leakage at room temperature is achieved.
Patent Information
- Application Number
- CN201911256030.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2019-12-09
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2039-12-09
AI Technical Summary
After exposure under a high temperature environment, light leakage is prone to occur in the concave portions of the polarizing plate and the periphery of the through-hole.
The polarizing plate design is adopted which includes a polyvinyl alcohol-based resin polarizer and a first thermoplastic resin film with low water absorption rate to ensure that the shrinkage force in the absorption axis direction of the polarizing plate is less than 1.3N.
It effectively suppresses the light leakage phenomenon of the polarizing plate when placed in room temperature atmosphere under high temperature environments.
Smart Images

Figure CN111308600B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate. Background Art
[0002] In recent years, the design of image display devices has been diversified. In response to this trend, polarizing plates are also required to adapt to various shapes.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2017-182017 Summary of the invention
[0006] Problems to be solved by the invention
[0007] When a polarizing plate having concave portions at its outer edge and / or through holes in its plane is left in a room temperature atmosphere after being exposed to a high temperature environment, light leakage may occur around the concave portions and through holes.
[0008] An object of the present invention is to provide a polarizing plate having a concave portion at an outer edge portion and / or a through hole in a plane in a plan view, wherein the polarizing plate can suppress light leakage generated when the plate is placed in a room temperature atmosphere after being exposed to a high temperature environment.
[0009] Means for solving problems
[0010] The present invention provides the following polarizing plate, image display device, and method for producing the polarizing plate.
[0011] [1] A polarizing plate comprising a polyvinyl alcohol-based resin polarizer and a first thermoplastic resin film provided on one surface thereof,
[0012] The water absorption rate of the first thermoplastic resin film is 0.1% or less.
[0013] The polarizing plate has a concave portion at the outer edge portion or a through hole in the plane when viewed from above.
[0014] The polyvinyl alcohol-based resin polarizer has a contraction force of 1.3 N or less per 2 mm width in the absorption axis direction.
[0015] [2] The polarizing plate according to [1], wherein the first thermoplastic resin film is an acrylic resin film or a polycycloolefin (COP) resin film.
[0016] [3] The polarizing plate according to [1] or [2], further comprising a second thermoplastic resin film provided on the other surface of the polyvinyl alcohol-based resin polarizer.
[0017] [4] A pressure-sensitive adhesive layer-attached polarizing plate comprising the polarizing plate according to any one of [1] to [3] and a pressure-sensitive adhesive layer provided on the first thermoplastic resin film side of the polarizing plate.
[0018] [5] The pressure-sensitive adhesive layer-attached polarizing plate according to claim 4, wherein the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer for bonding the polarizing plate to an image display element.
[0019] [6] An image display device comprising the polarizing plate according to any one of [1] to [3].
[0020] [7] A method for producing a polarizing plate according to any one of [1] to [3], comprising:
[0021] A preparation step of preparing a polyvinyl alcohol resin polarizer;
[0022] a laminating step of laminating the polyvinyl alcohol-based resin polarizer and a first thermoplastic resin film; and
[0023] The special-shaped processing step is to provide a concave portion at the outer edge of the polarizing plate or to provide a through hole in the surface.
[0024] The above-mentioned preparation step includes an annealing step.
[0025] Effects of the Invention
[0026] According to the present invention, even if the polarizing plate is a polarizing plate that includes a polyvinyl alcohol-based resin polarizer and also includes a first thermoplastic resin film with a water absorption rate of less than 0.1% on one surface thereof and has a concave portion at the outer edge portion or a through hole in the surface when viewed from above, since the shrinkage force of the polyvinyl alcohol-based resin polarizer in the absorption axis direction is within the above-mentioned range, light leakage caused by being exposed to a high temperature environment and then placed in a room temperature atmosphere can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.
[0028] Figure 2 It is a schematic plan view showing an example of a concave portion.
[0029] Figure 3 It is a schematic plan view showing a polarizing plate according to one embodiment of the present invention.
[0030] Figure 4 It is a schematic plan view showing an example of a through hole.
[0031] Figure 5 This is a schematic plan view showing an example of the relationship between the shrinkage direction and the stretching axis direction of the polarizing plate.
[0032] Figure 6 This is a schematic plan view showing an example of the relationship between the depth direction of the concave portion and the stretching direction.
[0033] Figure 7 This is a schematic cross-sectional view showing a polarizing plate according to one embodiment of the present invention.
[0034] Figure 8 This is a flow chart showing a method for producing a polarizing plate.
[0035] Fig. 9 This is a schematic diagram for explaining a method for evaluating light leakage of a polarizing plate.
[0036] Fig.10 Schematic diagram showing a polarizing plate produced in Examples.
[0037] Description of Reference Numerals
[0038] 10, 20, 40, 100, 201, 300 polarizing plate; 11, 12, 41, 301, 310 concave upper part; 302, 303, 304, 305 corner; 13, 306, 307 outer corner part; 14, 15, 308, 309, 311 inner corner part; 312 center of gravity; 313, 314 shortest distance; 21 through hole; 42 long side; 43 center point; 101 polarizing plate; 102 first thermoplastic resin film; 103 second thermoplastic resin film; 202 polarizing plate (unheated test); 203 backlight DETAILED DESCRIPTION
[0039] <Polarizing Plate>
[0040] The polarizing plate of the present invention is a polarizing plate comprising a polarizer and a first thermoplastic resin film disposed on one surface of the polarizer, and the polarizer is a polyvinyl alcohol resin polarizer as a polyvinyl alcohol resin film. The polarizing plate is a polarizing plate having a concave portion at the outer edge portion or a through hole in the plane, or both, when viewed from above. Hereinafter, the concave portion at the outer edge portion and the through hole in the plane are sometimes collectively referred to as a special-shaped portion. In this specification, viewing from above means observing from the thickness direction of the layer.
[0041] The polarizing plate of the present invention may be in a square shape or a rounded square shape when viewed from above. The rounded square shape means that at least one of the corners of the square shape presents a curved shape, that is, at least one of the corners of the square shape is rounded, and the square shape means that none of the four corners are rounded. In addition, in this specification, the square shape means a rectangular shape or a square shape. In the case where the polarizing plate is in a rounded square shape, at least one of the four corners of the polarizing plate may be rounded.
[0042] The radius of curvature of the rounded corner portion may be, for example, not less than 1 mm and not more than 10 mm, and preferably not less than 2 mm and not more than 8 mm.
[0043] like Figure 1 As shown in FIG. 1 , a polarizing plate according to an embodiment of the present invention is a rounded square polarizing plate 10 having concave portions 11 and 12 at the outer edge. Three of the four corners of the square polarizing plate 10 are rounded.
[0044] The concave portion 11 is a shape that is concave from the outer edge portion to the inside in a plan view, and the depth of the concave portion may be, for example, 0.1 mm or more, preferably 0.5 mm or more, and more preferably 1 mm or more. On the other hand, the depth of the concave portion is usually 7 mm or less.
[0045] The outer corner portion 13 constituting the concave portion 11 may be a right angle or not. In addition, the outer corner portion 13 may be rounded or not. When the outer corner portion 13 is rounded, the radius of curvature may be, for example, 0.1 mm or more and 10 mm or less, preferably 0.5 mm or more and 5 mm or less.
[0046] The inner corner portion 14 constituting the concave portion 11 may be a right angle or not. In addition, the inner corner portion 14 may be rounded or not. When the outer corner portion 14 is rounded, the radius of curvature may be, for example, 0.1 mm or more and 1 mm or less, preferably 0.5 mm or more and 5 mm or less.
[0047] The concave portion 12 is U-shaped in a plan view, and the depth of the concave portion can be, for example, 0.5 mm to 10 mm, preferably 1 mm to 8 mm.
[0048] The radius of curvature of the inner corner portion 15 constituting the concave portion 12 may be, for example, not less than 0.5 mm and not more than 15 mm, and preferably not less than 1 mm and not more than 10 mm.
[0049] The shape of the concave portion 11 is not particularly limited and may be, for example Figure 2 The shapes shown in (a) to (d).
[0050] like Figure 3 As shown in FIG. 1 , a polarizing plate according to another embodiment of the present invention is a rounded square polarizing plate 20 having a through hole 21 in a plane in a plan view. Four of the four corners of the square polarizing plate 20 are rounded.
[0051] The through hole 21 is Figure 3 The through holes are shown as circular in the figure, but are not limited to this, and may be, for example, elliptical, square, rounded square, or a combination of these shapes.
[0052] The radius of the through hole 21 may be, for example, not less than 0.5 mm and not more than 30 mm, and preferably not less than 1 mm and not more than 10 mm.
[0053] The shape of the through hole 21 is not particularly limited and may be, for example Figure 4 The number of through holes 21 may be one or two or more.
[0054] The inventors have found that when the polarizing plate has a deformed portion as described above, light leakage is likely to occur around the deformed portion. The light leakage of the present invention may be observed after the polarizing plate is exposed to a high temperature environment and then placed in a room temperature atmosphere. The high temperature environment conditions and the observation method are the conditions and methods described in the embodiment column described later.
[0055] The principle of light leakage is presumed as follows, but the present invention is not limited thereto. First, when the polarizing plate is heated, the polarizing plate shrinks along the stretching axis, that is, the absorption axis, and stress is applied to the first thermoplastic resin film by this shrinkage. Figure 5 As shown in (a), when the polarizing plate does not have a deformed portion, the contraction of the polarizer occurs in the absorption axis direction, and even if stress is applied to the first thermoplastic resin film, the absorption axis of the polarizer will not be disturbed, and light leakage will not occur. Figure 5 As shown in (b), when the polarizing plate has a non-uniform portion, the non-uniform portion shrinks along the shape of the non-uniform portion, and a portion is generated where the shrinkage direction of the polarizer is different from the direction of the absorption axis. In such a portion, the direction of the stress applied to the first thermoplastic resin film becomes a direction different from the absorption axis. It can be inferred that if the first thermoplastic resin film is subjected to stress in a direction different from the absorption axis, light leakage occurs in this portion.
[0056] The direction of the stretching axis (absorption axis) of the polarizer relative to the polarizing plate is not particularly limited. For example, when the polarizing plate is rectangular in a plan view, it can be a direction parallel to the long side direction, or it can be a direction parallel to the short side direction, or it can be a direction with an angle of 45±5 degrees with the long side direction (or the short side direction), and it can preferably be a direction of 45±2 degrees.
[0057] In addition, the inventors have found that when the shortest distance between the shaped portion and the center of gravity of the polarizing plate is, for example, 40 mm or more, preferably 50 mm or more, and more preferably 60 mm or more, light leakage is likely to occur around the shaped portion. It can be inferred that this is because the farther the position of the shaped portion is from the center of gravity, the greater the shrinkage of the polarizer of the shaped portion, the greater the stress on the first thermoplastic resin film in a direction different from the absorption axis, and the more likely it is that light leakage is likely to occur. Regarding the center of gravity of the polarizing plate, for example, when the polarizing plate is square, it can be defined as the intersection of the diagonal lines. In the case where the polarizing plate is in a rounded square shape or loses an angle due to a concave portion, it can be set to the intersection when the rounded portion is replaced by the corner portion and the diagonal line is formed from the corner portion.
[0058] It was further found that when the irregular portion is located in an area where the distance from the center of gravity of the polarizing plate exceeds 20% of the area equivalent radius, light leakage is likely to occur around the irregular portion. It can be inferred that this is because: the farther the position of the irregular portion is from the center of gravity, the greater the shrinkage of the polarizing plate in the irregular portion, the greater the stress on the first thermoplastic resin film in a direction different from the absorption axis, and the more likely it is that light leakage will occur. The 20% area equivalent radius from the center of gravity means that when a circle centered on the center of gravity is overlapped on the polarizing plate in a plan view, the area of the circle is equivalent to the radius of a circle that is 20% of the total area of the polarizing plate.
[0059] The polarizing plate may have a irregular portion in a region exceeding 30% of the area equivalent radius from the center of gravity of the polarizing plate, or may have a irregular portion in a region exceeding 40% of the area equivalent radius.
[0060] Furthermore, the inventors have found that when the depth direction of the concave portion of the outer edge of the polarizing plate is orthogonal to the stretching axis direction (contraction direction), light leakage tends to occur. For example, as such a polarizing plate, there are: Figure 6 The polarizing plate shown in the plan view is a rounded rectangular shape and has a concave portion 41 . The polarizing plate has the concave portion 41 on the long side 42 . The concave portion 41 includes the center point 43 of the long side 42 , and the long side 42 is in the absorption axis direction.
[0061] The thickness of the polarizing plate may generally be 5 μm or more and 200 μm or less, may be 150 μm or less, or may be 120 μm or less.
[0062] The polarizing plate includes a polarizer and a first thermoplastic resin film provided on one surface of the polarizer. Figure 7The polarizing plate 100 shown includes a polarizing plate 101 and a first thermoplastic resin film 102 located on one surface of the polarizing plate 101. The polarizing plate 100 may further include a second thermoplastic resin film 103 on the other surface of the polarizing plate 101. Hereinafter, the first thermoplastic resin film 102 and the second thermoplastic resin film 103 are also collectively referred to as thermoplastic resin films.
[0063] [Polarizing plate]
[0064] The polarizer 101 is a polyvinyl alcohol resin polarizer as a polyvinyl alcohol resin film, and specifically, it can be, for example, a polarizer in which a dichroic pigment is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol resin film. Such a polarizer can be manufactured according to the manufacturing method of the polarizer described later. The polarizer 101 can be an absorption-type polarizer having the property of absorbing linear polarized light having a vibration plane parallel to the absorption axis and transmitting linear polarized light having a vibration plane orthogonal to the absorption axis (parallel to the transmission axis). The polarizer 101 can be used as a polarizing plate 100 by bonding a first thermoplastic resin film 102 to one surface thereof with an adhesive or a bonding agent.
[0065] The shrinkage force per 2 mm width in the absorption axis direction of the polarizer 101 (hereinafter also referred to as "shrinkage force") is 1.3 N or less. When the shrinkage force of the polarizer 101 is 1.3 N or less, there is a tendency that light leakage is not easy to occur around the irregular portion of the polarizing plate 100. As described above, it can be inferred that the light leakage is caused by the depolarization caused by the strain of the first thermoplastic resin film with low water absorption rate caused by the shrinkage of the polarizer. With this in mind, the inventors have found that light leakage can be suppressed by reducing the shrinkage force of the polarizer. The shrinkage force of the polarizer 101 is measured according to the measurement method described in the embodiment column described later.
[0066] From the viewpoint of suppressing light leakage, the shrinkage force of the polarizer 101 is preferably 1.2 N or less, more preferably 0.9 N or less, further preferably 0.8 N or less, and particularly preferably 0.7 N or less. On the other hand, the shrinkage force of the polarizer 101 is usually 0.1 N or more. As a method for setting the shrinkage force of the polarizer 101 to 1.3 N or less, the adjustment of the boric acid concentration in the cross-linking step described later or the implementation of the annealing treatment can be cited.
[0067] The thickness of the polarizer 101 is usually 20 μm or less, preferably 18 μm or less, and more preferably 15 μm or less. Reducing the thickness of the polarizer 101 is advantageous for thinning the polarizing plate 100. The thickness of the polarizer 101 is usually 1 μm or more, and can be, for example, 5 μm or more.
[0068] The thickness of the polarizing plate 101 can be controlled by, for example, selecting a polyvinyl alcohol-based resin film, adjusting a stretch ratio, and the like.
[0069] [Method for producing polarizing plate]
[0070] A method for manufacturing the polarizing plate 101 will be described with reference to the drawings. Figure 8 The manufacturing method shown may include the following steps:
[0071] A swelling step S10 of immersing the polyvinyl alcohol-based resin film in a swelling tank containing a treatment liquid containing water;
[0072] a dyeing step S20 of immersing the polyvinyl alcohol-based resin film in a dyeing tank containing a treatment liquid containing a dichroic dye to dye the film;
[0073] A cross-linking step S30 of immersing the polyvinyl alcohol-based resin film in a cross-linking tank containing a treatment liquid containing a cross-linking agent to perform a cross-linking treatment;
[0074] a cleaning step S40 of immersing the polyvinyl alcohol-based resin film in a cleaning tank; and
[0075] Drying step S50.
[0076] The polyvinyl alcohol-based resin film is subjected to uniaxial stretching treatment (stretching step) in one or more stages of the polarizing plate production process, more specifically, in one or more stages from before the swelling step S10 to the cross-linking step S30 .
[0077] The manufacturing method may further include other steps besides the above, and a specific example thereof may be as follows Figure 8 Annealing step S60 etc. as shown.
[0078] The various treatment steps included in the manufacturing method of the present invention can be continuously implemented by continuously conveying the polyvinyl alcohol-based resin film as the raw material film along the film conveying path of the polarizing plate manufacturing apparatus. The film conveying path is equipped with equipment (treatment tank or furnace, etc.) for implementing the above-mentioned various treatment steps according to these implementation orders.
[0079] The film conveying path can be constructed by placing guide rollers, clamping rollers, etc. at appropriate positions on the basis of the above-mentioned equipment. For example, guide rollers can be placed before and after each treatment tank or in the treatment tank, thereby allowing the film to be introduced into the treatment tank, immersed in the treatment tank, and pulled out of the treatment tank. More specifically, by arranging two or more guide rollers in each treatment tank and conveying the film along these guide rollers, the film can be immersed in each treatment tank.
[0080] As for the polyvinyl alcohol resin constituting the polyvinyl alcohol resin film as the raw material film, the polyvinyl alcohol resin obtained by saponifying the polyvinyl acetate resin can be used. As the polyvinyl acetate resin, in addition to the homopolymer of vinyl acetate, that is, polyvinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith can also be exemplified. As other monomers copolymerizable with vinyl acetate, for example, unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, (meth) acrylamides having an ammonium group, etc. can be cited. The saponification degree of the polyvinyl alcohol resin is generally about 85 mol% or more, preferably about 90 mol% or more, and more preferably about 99 mol% or more. In this specification, "(meth) acrylic acid" refers to at least one selected from acrylic acid and methacrylic acid. The same is true for "(meth) acryloyl".
[0081] The polyvinyl alcohol-based resin may be modified, and for example, polyvinyl formal, polyvinyl acetal, polyvinyl butyral, etc. modified with aldehydes may be used.
[0082] The average degree of polymerization of the polyvinyl alcohol resin is preferably 100 or more and 10000 or less, more preferably 1500 or more and 8000 or less, and further preferably 2000 or more and 5000 or less. The average degree of polymerization of the polyvinyl alcohol resin can be obtained according to JIS K 6726 (1994). When the average degree of polymerization is less than 100, it is difficult to obtain the desired polarization performance, and when it exceeds 10000, the film processability is sometimes deteriorated.
[0083] The thickness of the polyvinyl alcohol-based resin film is, for example, about 10 μm or more and 50 μm or less. From the viewpoint of making the thickness of the polarizer 15 μm or less, it is preferably 40 μm or less, and more preferably 30 μm or less.
[0084] The polyvinyl alcohol resin film as the raw material film can be prepared as a roll (wound product) of a long unstretched or stretched polyvinyl alcohol resin film, for example. In this case, the polarizer can also be obtained in the form of a long strip. Each step is described in detail below.
[0085] (1) Swelling step S10
[0086] The swelling treatment in this step is a treatment performed as required for the purpose of removing foreign matter from the polyvinyl alcohol resin film as the raw material film, removing plasticizers, imparting easy dyeing properties, plasticizing the film, etc. Specifically, it can be a treatment in which the polyvinyl alcohol resin film is immersed in a swelling tank containing a treatment liquid containing water. The film can be immersed in one swelling tank or in two or more swelling tanks in sequence. The film can be subjected to uniaxial stretching treatment before the swelling treatment, during the swelling treatment, or before and during the swelling treatment.
[0087] The treatment liquid contained in the swelling tank may be water (for example, pure water), or an aqueous solution to which a water-soluble organic solvent such as alcohol is added.
[0088] The temperature of the treatment liquid contained in the swelling tank when immersing the membrane is usually above 10°C and below 70°C, preferably above 15°C and below 50°C, and the immersion time of the membrane is usually above 10 seconds and below 600 seconds, preferably above 20 seconds and below 300 seconds.
[0089] (2) Dyeing step S20
[0090] The dyeing process in this process is a process for adsorbing and orienting the dichroic pigment to the polyvinyl alcohol resin film. Specifically, the polyvinyl alcohol resin film can be immersed in a dyeing tank that accommodates a treatment solution containing a dichroic pigment. The film can be immersed in one dyeing tank or in two or more dyeing tanks in sequence. In order to improve the dyeability of the dichroic pigment, the film supplied to the dyeing process can be subjected to at least a certain degree of uniaxial stretching. It is also possible to replace the uniaxial stretching before the dyeing process and perform uniaxial stretching during the dyeing process, or on the basis of the uniaxial stretching before the dyeing process, also perform uniaxial stretching during the dyeing process.
[0091] The dichroic pigment can be iodine or dichroic organic dye.The specific example of dichroic organic dye comprises red BR, red LR, red R, pink LB, ruby red BL, red date GS, sky blue LG, lemon yellow, blue BR, blue 2R, navy blue RY, green LG, purple LB, purple B, black H, black B, black GSP, yellow 3G, yellow R, orange LR, orange 3R, scarlet GL, scarlet KGL, Congo red, bright purple BK, fast blue (SupraBlue) G, fast blue GL, fast orange (Supra Orange) GL, direct sky blue, direct fast orange S, fast black.The dichroic pigment can only be used alone 1 kind, also can use 2 or more kinds in combination.
[0092] When iodine is used as a dichroic pigment, the treatment solution contained in the dyeing tank can use an aqueous solution containing iodine and potassium iodide. Other iodides such as zinc iodide can be used instead of potassium iodide, and potassium iodide and other iodides can also be used in combination. In addition, compounds other than iodides, such as boric acid, zinc chloride, cobalt chloride, etc., can also coexist. When boric acid is added, it is different from the cross-linking treatment described later in that iodine is included. The content of iodine in the above-mentioned aqueous solution is usually 0.01 mass parts or more and 1 mass parts or less relative to 100 mass parts of water. In addition, the content of iodides such as potassium iodide is usually 0.5 mass parts or more and 20 mass parts or less relative to 100 mass parts of water. As mentioned above, the treatment solution contained in the dyeing tank can contain zinc salts.
[0093] The temperature of the treatment liquid contained in the dyeing tank when the film is immersed is usually 10°C to 45°C, preferably 10°C to 40°C, more preferably 20°C to 35°C, and the immersion time of the film is usually 30 seconds to 600 seconds, preferably 60 seconds to 300 seconds.
[0094] When a dichroic organic dye is used as the dichroic pigment, the treatment liquid contained in the dyeing tank may be an aqueous solution containing the dichroic organic dye. The content of the dichroic organic dye in the aqueous solution is usually 1×10 -4 parts by mass or more and 10 parts by mass or less, preferably 1×10 -3 The dyeing tank may contain at least 1 part by mass and at most 1 part by mass. Dyeing aids and the like may also coexist in the dyeing tank, and may contain inorganic salts such as sodium sulfate, surfactants, and the like. The dichroic organic dye may be used alone or in combination of two or more. The temperature of the treatment liquid contained in the dyeing tank when the film is immersed is, for example, 20°C or more and 80°C or less, preferably 30°C or more and 70°C or less, and the immersion time of the film is usually 30 seconds or more and 600 seconds or less, preferably 60 seconds or more and 300 seconds or less.
[0095] (3) Cross-linking step S30
[0096] The crosslinking treatment of the polyvinyl alcohol-based resin film after the dyeing step with a crosslinking agent is performed for the purpose of water resistance and color tone adjustment based on crosslinking. Specifically, it can be a treatment in which the film after the dyeing step is immersed in a treatment liquid contained in a crosslinking tank containing a crosslinking agent.
[0097] The film may be immersed in one cross-linking tank or may be immersed in two or more cross-linking tanks in sequence. During the cross-linking treatment, a uniaxial stretching treatment may be performed.
[0098] As the cross-linking agent, boric acid, glyoxal, glutaraldehyde, etc. can be listed, preferably boric acid. It is also possible to use two or more cross-linking agents. The content of boric acid in the treatment solution accommodated in the cross-linking tank is usually 0.1 mass parts or more and 15 mass parts or less relative to 100 mass parts of water, and from the viewpoint of the shrinkage force of the polarizer, it is preferably 1 mass part or more and 10 mass parts or less.
[0099] When the dichroic pigment is iodine, the treatment solution housed in the cross-linking tank preferably also contains iodide on the basis of boric acid. The content of the iodide in the treatment solution housed in the cross-linking tank is usually more than 0.1 mass parts and less than 15 mass parts relative to 100 mass parts of water, preferably more than 5 mass parts and less than 12 mass parts. As iodide, potassium iodide, zinc iodide etc. can be listed. In addition, compounds other than iodide, for example zinc chloride, cobalt chloride, zirconium chloride, sodium thiosulfate, potassium sulfite, sodium sulfate etc. can also be coexisted in the cross-linking tank.
[0100] The temperature of the treatment liquid contained in the crosslinking tank when the film is immersed is usually 50°C to 85°C, preferably 50°C to 70°C, and the immersion time of the film is usually 10 seconds to 600 seconds, preferably 20 seconds to 300 seconds.
[0101] In the cross-linking step S30, the cross-linking tank may have more than two tanks. In this case, the composition and temperature of the treatment solution contained in each cross-linking tank may be the same or different. The treatment solution contained in the cross-linking tank may have a concentration and temperature of a cross-linking agent and an iodide corresponding to the purpose of impregnating the polyvinyl alcohol-based resin film. The cross-linking treatment for water resistance based on cross-linking and the cross-linking treatment for color tone adjustment (color correction) may be performed in multiple steps (e.g., multiple tanks).
[0102] Generally speaking, in the case of implementing both a cross-linking treatment for water resistance based on cross-linking and a cross-linking treatment for color tone adjustment (color correction), the tank (color correction tank) for implementing the cross-linking treatment for color tone adjustment (color correction) is arranged in the rear section. The temperature of the treatment liquid contained in the color correction tank is, for example, above 10°C and below 55°C, preferably above 20°C and below 50°C. The content of the cross-linking agent in the treatment liquid contained in the color correction tank is, for example, above 1 part by mass and below 5 parts by mass relative to 100 parts by mass of water. The content of iodide in the treatment liquid contained in the color correction tank is, for example, above 3 parts by mass and below 30 parts by mass relative to 100 parts by mass of water.
[0103] As described above, in the manufacture of the polarizer, the polyvinyl alcohol-based resin film is subjected to uniaxial stretching treatment in any one or two or more stages from before the swelling step S10 to the crosslinking step S30 (stretching step, Figure 1 ). From the viewpoint of improving the dyeability of the dichroic dye, the film provided for the dyeing process is preferably a film that has been subjected to at least a certain degree of uniaxial stretching treatment, or, preferably, a uniaxial stretching treatment is performed during the dyeing process instead of the uniaxial stretching treatment before the dyeing process, or a uniaxial stretching treatment is performed during the dyeing process on the basis of the uniaxial stretching treatment before the dyeing process.
[0104] The uniaxial stretching process can be any one of dry stretching in air and wet stretching in a groove, or both. The uniaxial stretching process can be roller-to-roll stretching, hot roller stretching, tenter stretching, etc., which are performed longitudinally uniaxially by giving a circumferential speed difference between two clamping rollers, preferably including roller-to-roll stretching. The stretching ratio (in the case of stretching treatment in more than two stages, their cumulative stretching ratio) based on the original film is more than 3 times and about 8 times or less. In order to give good polarization characteristics, the stretching ratio is preferably more than 4 times, more preferably more than 5 times.
[0105] The polarizer obtained by undergoing the crosslinking step S30 contains a boron component. There is a tendency that the less the content of the boron component is, the smaller the shrinkage force is. In order to reduce the content of the boron component, it is only necessary to reduce the boric acid content in the treatment solution of the crosslinking tank or shorten the immersion time in the crosslinking tank.
[0106] (4) Cleaning step S40
[0107] The cleaning process in this process is a process implemented as needed for the purpose of removing excess cross-linking agents, dichroic pigments and other chemical reagents attached to the polyvinyl alcohol resin film, and is a process of cleaning the polyvinyl alcohol resin film after the cross-linking process using a cleaning solution containing water. Specifically, it can be a process in which the polyvinyl alcohol resin film after the cross-linking process is immersed in a treatment solution (cleaning solution) contained in a cleaning tank. The film can be immersed in one cleaning tank, or it can be immersed in more than two cleaning tanks in sequence. Alternatively, the cleaning process can be a process in which the polyvinyl alcohol resin film after the cross-linking process is sprayed with a cleaning solution in the form of a spray, or the above-mentioned dipping and spraying can be combined.
[0108] The cleaning liquid may be water (eg, pure water) or an aqueous solution to which a water-soluble organic solvent such as alcohol is added. The temperature of the cleaning liquid may be, for example, about 5° C. or higher and 40° C. or lower.
[0109] The cleaning step S40 is an optional step and may be omitted. It is preferred that the film after the cleaning step S40 is subjected to a drying step S50 .
[0110] (5) Drying step S50
[0111] The drying step S50 is a region for drying the polyvinyl alcohol-based resin film after the cleaning step S40. The polyvinyl alcohol-based resin film after the cleaning step S40 is introduced into the drying step S50 while being continuously conveyed, so that a drying treatment can be performed, thereby obtaining a polarizing plate.
[0112] The drying process is carried out using a film drying device (heating device). A suitable example of the drying device is a drying furnace. The drying furnace is preferably a drying furnace capable of controlling the temperature in the furnace. The drying furnace is, for example, a hot air oven that can increase the temperature in the furnace by supplying hot air. In addition, the drying process using the drying device can be a process in which the polyvinyl alcohol-based resin film after the cleaning step S40 is brought into close contact with one or more heating bodies having a convex curved surface, or a process in which the film is heated using a heater.
[0113] Examples of the heating element include rollers (such as guide rollers also serving as heating rollers) that have a heat source (such as a heat medium such as hot water, or an infrared heater) inside and can increase the surface temperature. Examples of the heater include infrared heaters, halogen heaters, and panel heaters.
[0114] The drying temperature (eg, the temperature inside the drying furnace, the surface temperature of the heat roll, etc.) is usually 30° C. to 100° C., preferably 50° C. to 90° C. The drying time is not particularly limited, but is, for example, 30 seconds to 600 seconds.
[0115] (6) Annealing step S60
[0116] In order to reduce the shrinkage force of the polarizer, an annealing step S60 may be performed after the drying step S50 and after the polarizer is brought to room temperature.
[0117] Regarding the annealing process, for example, a first substrate film is laminated on one side of the polarizer through a pure water layer using its surface tension, and a second substrate film is laminated on the other side through a pure water layer using its surface tension, and heated, thereby removing the moisture of the pure water layer. The drying temperature is usually below 70°C to 90°C, and the time is usually 0.5 minutes to 2 minutes. A three-layer laminate is obtained by drying, in which a first substrate film that can be peeled off from the polarizer is laminated on one side of the polarizer, and a second substrate film that can be peeled off from the polarizer is laminated on the other side. Then, the second substrate film is peeled off from the three-layer laminate to form a laminate in which only the first substrate film is laminated on one side of the polarizer, and the two-layer laminate is clamped with 2 sheets of dust-free paper, and heated in this state, thereby performing an annealing treatment. The heating temperature is usually 70°C to 110°C, preferably 80°C to 100°C, and the heating time is usually 0.5 hours to 24 hours, preferably 2 hours to 12 hours. Since the polarizer is heated while being held between the bonded releasable first base film and the dust-free paper which is merely overlapped but not bonded, stress of the polarizer is easily relaxed, and shrinkage force can be reduced.
[0118] The first base film and the second base film can be easily peeled off. The first base film and the second base film can be peeled off just before the thermoplastic resin film is laminated in the laminating step of the thermoplastic resin film described later.
[0119] The first substrate film may be, for example, a TAC film, and the second substrate film may be, for example, a PMMA film.
[0120] Heating can be performed using, for example, a common heating furnace. Examples of the heating furnace include a temperature-controllable hot air oven, an infrared heater, and the like.
[0121] Through the above steps, a polarizing plate in which a dichroic dye is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol-based resin film can be obtained.
[0122] The obtained polarizing plate may be directly conveyed to the next polarizing plate production step (step of laminating a thermoplastic resin film to one or both surfaces of the polarizing plate), for example.
[0123] [First thermoplastic resin film]
[0124] The water absorption rate of the first thermoplastic resin film 102 (hereinafter also referred to as "water absorption rate") is 0.1% or less. Generally speaking, there is a tendency that light leakage is less likely to occur when the water absorption rate of the first thermoplastic resin film 102 is high. It can be inferred that this is because: when the water absorption rate of the first thermoplastic resin film 102 is high, when it is placed in the room temperature atmosphere after being exposed to a high temperature environment, the moisture in the atmosphere is absorbed by the first thermoplastic resin film or the polarizer, and the first thermoplastic resin film or the polarizer expands, and the stress is relaxed. However, according to the present invention, even when the water absorption rate of the first thermoplastic resin film 102 is 0.1% or less, by reducing the shrinkage rate of the polarizer 101 as described above, the occurrence of light leakage can be easily suppressed. The water absorption rate is the amount of water contained in the film, and is expressed as the ratio of the mass of water to the mass of the film. The water absorption rate of the first thermoplastic resin film 102 is obtained by the measurement method described in the embodiment column described later. The water absorption of the first thermoplastic resin film 102 may be, for example, 0.05% or less. On the other hand, the water absorption of the first thermoplastic resin film 102 is usually 0% or more, and may be, for example, 0.0001% or more, or 0.001% or more.
[0125] As the first thermoplastic resin film 102, for example, a polyolefin resin such as a polyolefin resin (polypropylene resin, etc.) or a polycycloolefin resin (norbornene resin, etc.); a transparent resin film formed by a (meth) acrylic resin such as a polymethyl methacrylate resin, etc., can be cited. Among them, from the viewpoint of optical light resistance and dimensional stability, a (meth) acrylic resin film or a polycycloolefin (COP) resin film is preferred. In particular, since the water absorption rate of the polycycloolefin (COP) resin film is low, there is a tendency that the polarizing plate of the present invention is effective when a polycycloolefin (COP) resin film is used as the first thermoplastic resin film 102. In general, the water absorption rate of the film composed of the polycycloolefin resin (COP) is low, so the polarizing plate including the film has the following tendency: after being exposed to high temperature, light leakage is likely to occur around the irregular portion even after being left at room temperature. However, according to the present invention, even if the first thermoplastic resin film 102 is a film formed of such a polycycloolefin-based resin, there is a tendency that light leakage is less likely to occur around the irregular portion.
[0126] From the viewpoint of thinning the polarizing plate 100, the thickness of the first thermoplastic resin film 102 is preferably thin. If it is too thin, there is a tendency for the strength to decrease and the processability to deteriorate. Therefore, it is preferably 5 μm to 150 μm, more preferably 5 μm to 100 μm, and further preferably 10 μm to 50 μm.
[0127] The first thermoplastic resin film 102 may function as a protective film. In addition, any one or both of the first thermoplastic resin film 102 and the second thermoplastic resin film 103 described later may also be a protective film having optical functions such as a phase difference film and a brightness enhancement film. For example, a phase difference film having an arbitrary phase difference value may be prepared by stretching a transparent resin film formed of the above-mentioned material (uniaxial stretching or biaxial stretching, etc.) or forming a liquid crystal layer on the film.
[0128] When the polarizing plate 100 is disposed in an image display device, the polarizing plate 100 may be attached to the image display device in such a manner that the first thermoplastic resin film 102 faces the image display device side. Alternatively, the polarizing plate 100 may be attached to the image display device in such a manner that the first thermoplastic resin film 102 faces the outer side of the image display device. The polarizing plate 100 is preferably attached to the image display device in such a manner that the first thermoplastic resin film 102 faces the image display device side.
[0129] The first thermoplastic resin film 102 and the second thermoplastic resin film 103 described later can be thermoplastic resin films formed with a hard coating. The hard coating can be formed on one surface of the thermoplastic resin film, or on both surfaces. By providing a hard coating, a thermoplastic resin film with improved hardness and scratch resistance can be made. The hard coating is, for example, a cured layer of an ultraviolet curable resin. As ultraviolet curable resins, for example, acrylic resins, silicone resins, polyester resins, urethane resins, amide resins, epoxy resins, etc. can be cited. In order to improve the strength, the hard coating can contain additives. The additives are not limited, and inorganic particles, organic particles, or mixtures thereof can be cited.
[0130] [Second Thermoplastic Resin Film]
[0131] The second thermoplastic resin film 103 may be of the same type or different type as the film exemplified in the description of the first thermoplastic resin film 102. The water absorption rate of the second thermoplastic resin film 103 may be 0.1% or less, or may exceed 0.1%.
[0132] The second thermoplastic resin film 103 may be a transparent resin film formed from a thermoplastic resin, for example, a polyolefin resin such as a polyalkene resin (polypropylene resin, etc.), a polycycloolefin resin (norbornene resin, etc.); a cellulose ester resin such as triacetyl cellulose or diacetyl cellulose; a polyester resin such as polyethylene terephthalate, polyethylene naphthalate, or polybutylene terephthalate; a polycarbonate resin; a (meth)acrylic resin such as a polymethyl methacrylate resin; or a mixture, copolymer, or the like thereof.
[0133] The second thermoplastic resin film 103 may have a function as a protective film. When the polarizing plate 100 is disposed in an image display device, the polarizing plate 100 may be attached to the image display device in such a manner that the second thermoplastic resin film 103 is on the outside of the image display device. In addition, the polarizing plate 100 may also be attached to the image display device in such a manner that the second thermoplastic resin film 103 is on the image display device side. The polarizing plate 100 is preferably attached to the image display device in such a manner that the second thermoplastic resin film 103 is on the outside of the image display device.
[0134] [Other components of polarizing plate]
[0135] (1) Optical functional film
[0136] The polarizing plate 100 may include other optically functional films in addition to the polarizing plate 101 for imparting desired optical functions, and a suitable example thereof is a retardation film.
[0137] As described above, the first thermoplastic resin film 102 and / or the second thermoplastic resin film 103 may also serve as a phase difference film, or a phase difference film may be laminated separately from these films. In the latter case, the phase difference film may be laminated on the outer surface of the first thermoplastic resin film 102 and / or the second thermoplastic resin film 103 via an adhesive layer or a bonding agent layer.
[0138] Examples of the retardation film include a birefringent film composed of a stretched film of a light-transmitting thermoplastic resin; a film in which discotic liquid crystal or nematic liquid crystal is oriented and fixed; and a retardation film in which the liquid crystal layer is formed on a substrate film.
[0139] The base film is usually a film formed of a thermoplastic resin, and an example of the thermoplastic resin is a cellulose ester resin such as triacetyl cellulose.
[0140] Examples of other optically functional films (optical members) that may be included in the polarizing plate 100 include a light-collecting plate, a brightness enhancement film, a reflective layer (reflective film), a semi-transmissive reflective layer (semi-transmissive reflective film), a light diffusion layer (light diffusion film), etc. These are generally provided when the polarizing plate is a polarizing plate disposed on the back side (backlight side) of the liquid crystal unit.
[0141] (2) Adhesive layer
[0142] The polarizing plate 100 may be provided with an adhesive layer to form a polarizing plate with an adhesive layer.
[0143] As the adhesive layer, there can be mentioned an adhesive layer for bonding the polarizing plate 100 to an image display element such as a liquid crystal cell, an organic EL display element, or other optical member. Figure 7 The outer surface of the first thermoplastic resin film 102 in the polarizing plate 100 having the structure shown. The adhesive layer may also be laminated on Figure 7 The outer surface of the second thermoplastic resin film 103 in the polarizing plate 100 having the structure shown. The adhesive layer is preferably laminated on the outer surface of the first thermoplastic resin film 102.
[0144] As the adhesive used in the adhesive layer, an adhesive having a base polymer of (meth) acrylic resin, silicone resin, polyester resin, polyurethane resin, polyether resin, etc. can be used. Among them, (meth) acrylic adhesives are preferred from the viewpoints of transparency, adhesion, reliability, weather resistance, heat resistance, reprocessability, etc.
[0145] In the (meth)acrylic adhesive, a (meth)acrylic resin having a weight average molecular weight of 100,000 or more obtained by blending a (meth)acrylic acid alkyl ester having an alkyl group having 20 or less carbon atoms such as methyl, ethyl, n-butyl, isobutyl or tert-butyl and a functional group-containing (meth)acrylic acid monomer such as (meth)acrylic acid or hydroxyethyl (meth)acrylate so that the glass transition temperature is preferably 25° C. or less, more preferably 0° C. or less is useful as a base polymer.
[0146] The adhesive layer can be formed on the polarizing plate by, for example, dissolving or dispersing the adhesive composition in an organic solvent such as toluene or ethyl acetate to prepare an adhesive solution, and applying the solution directly to the target surface of the polarizing plate to form the adhesive layer; or forming the adhesive layer in a sheet form on a release-treated diaphragm in advance, and then transferring the sheet to the target surface of the polarizing plate.
[0147] The thickness of the pressure-sensitive adhesive layer is determined based on its adhesive strength and the like, and is appropriately in the range of 1 μm to 50 μm, and is preferably in the range of 2 μm to 40 μm.
[0148] The polarizing plate may include the above-mentioned separator. The separator may be a film formed of polyethylene resins such as polyethylene, polypropylene resins such as polypropylene, polyester resins such as polyethylene terephthalate, etc. Among them, a stretched film of polyethylene terephthalate is preferred.
[0149] The adhesive layer may contain fillers including glass fibers, glass beads, resin beads, metal powders or other inorganic powders, pigments, colorants, antioxidants, ultraviolet absorbers, antistatic agents, and the like as necessary.
[0150] Examples of the antistatic agent include ionic compounds, conductive fine particles, and conductive polymers, and an ionic compound is preferably used.
[0151] The cationic component constituting the ionic compound may be an inorganic cation or an organic cation.
[0152] Examples of the organic cation include pyridinium cation, imidazolium cation, ammonium cation, sulfonium cation, phosphonium cation, piperidinium cation, and pyrrolidinium cation. Examples of the inorganic cation include lithium ion and potassium ion.
[0153] On the other hand, as the anion component constituting the ionic compound, it can be an inorganic anion or an organic anion. From the aspect of imparting an ionic compound with excellent antistatic performance, an anion component containing fluorine atoms is preferred. As the anion component containing fluorine atoms, hexafluorophosphate anion [(PF6 -)], bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - ] anion, bis(fluorosulfonyl)imide anion [(FSO2)2N - ] anions, etc.
[0154] (3) Protective film
[0155] The polarizing plate 100 may include a protective film for protecting its surface (typically, the surface of the first thermoplastic resin film 102 or the second thermoplastic resin film 103). The protective film is peeled off together with the adhesive layer after the polarizing plate is attached to an image display device or other optical components.
[0156] The protective film is composed of, for example, a base film and an adhesive layer laminated thereon. The above description is used for the adhesive layer.
[0157] The resin constituting the substrate film may be a thermoplastic resin such as polyethylene resin such as polyethylene, polypropylene resin such as polypropylene, polyester resin such as polyethylene terephthalate or polyethylene naphthalate, or polycarbonate resin, and preferably a polyester resin such as polyethylene terephthalate.
[0158] <Method for Manufacturing Polarizing Plate>
[0159] The manufacturing method of the polarizing plate 100 may include: a preparation step of preparing the polarizing plate 101; a laminating step of laminating the polarizing plate 101 and the first thermoplastic resin film 102; and a special-shaped processing step of providing a concave portion at the outer edge of the polarizing plate or providing a through hole in the surface, and the preparation step may include an annealing step. In addition, the special-shaped processing step may be a step of providing a concave portion at the outer edge of the polarizing plate and providing a through hole in the surface.
[0160] When the polarizing plate 100 further includes a second thermoplastic resin film 103 , the manufacturing method may further include a second bonding step of bonding the second thermoplastic resin film 103 to the other surface of the polarizing plate 101 .
[0161] [Preparation process]
[0162] The preparation step may include the steps described above for the method for producing the polarizing plate. The preparation step of the method for producing the polarizing plate of the present invention may include an annealing step.
[0163] [Lamination process]
[0164] In the laminating process, the thermoplastic resin film can be laminated (laminated) on both sides of the polarizer 101 through an adhesive. As the adhesive used in the laminating of the polarizer 101 and the thermoplastic resin film, active energy ray-curing adhesives such as ultraviolet curing adhesives, aqueous solutions of polyvinyl alcohol resins or aqueous solutions to which a crosslinking agent is added, and water-based adhesives such as urethane emulsion adhesives can be listed. When a thermoplastic resin film is laminated on both sides of the polarizer 101, the adhesives forming the two adhesive layers can be of the same type or of different types. For example, when a thermoplastic resin film is laminated on both sides, an aqueous adhesive can be used to laminate on one side and an active energy ray-curing adhesive can be used to laminate on the other side. The ultraviolet curing adhesive can be a mixture of a free radical polymerizable (meth) acrylic compound and a photoradical polymerization initiator, a mixture of a cationic polymerizable epoxy compound and a photocationic polymerization initiator, etc. Furthermore, a cationically polymerizable epoxy compound and a radically polymerizable (meth)acrylic compound may be used in combination, and a photocationic polymerization initiator and a photoradical polymerization initiator may be used in combination as the initiator.
[0165] When an active energy ray-curable adhesive is used, the adhesive is cured by irradiating the active energy ray after lamination. The light source of the active energy ray is not particularly limited, and preferably active energy rays (ultraviolet rays) having a luminous distribution below a wavelength of 400 nm are used. Specifically, a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, etc. are preferably used.
[0166] In order to improve the adhesion between the polarizer 101 and the thermoplastic resin film, the bonding surface of the polarizer 101 and / or the thermoplastic resin film can be subjected to surface treatment such as corona treatment, flame treatment, plasma treatment, ultraviolet irradiation treatment, primer coating treatment, saponification treatment, etc. before bonding the polarizer 101 and the thermoplastic resin film.
[0167] As described above, the polarizing plate 100 of the present invention can also be produced by laminating a thermoplastic resin film on the polarizer 101 as a single-layer film, but is not limited to this method. It can also be produced by a method using a substrate film as described in Japanese Patent Publication No. 2009-98653. The latter method is advantageous for obtaining a polarizing plate having a polarizer (polarizer layer) in the form of a thin film, and can include, for example, the following steps.
[0168] a resin layer forming step of applying a coating liquid containing a polyvinyl alcohol-based resin on at least one surface of a base film and then drying the coating liquid to form a polyvinyl alcohol-based resin layer to obtain a laminated film;
[0169] a stretching step of stretching the laminated film to obtain a stretched film;
[0170] a dyeing step of dyeing the polyvinyl alcohol-based resin layer as a stretched film with a dichroic dye to form a polarizer layer (equivalent to a polarizer), thereby obtaining a polarizing laminated film;
[0171] A first laminating step of laminating a thermoplastic resin film to a polarizer layer of a polarizing laminated film using an adhesive to obtain a laminated film; and
[0172] The peeling step is to peel off and remove the base film from the bonding film to obtain a polarizing plate with a thermoplastic resin film on one side.
[0173] When thermoplastic resin films are laminated on both sides of the polarizer 101 layer (polarizer), a second laminating step of laminating a second thermoplastic resin film to the polarizer surface of the polarizing plate having the first thermoplastic resin film on one side thereof using an adhesive is included.
[0174] In the above method using a substrate film, the dyeing step of obtaining a polarizing laminated film (for example, after the crosslinking step or after the washing step in the dyeing step of obtaining a polarizing laminated film) may include an annealing step and a drying step. The polarizing laminated film, the polarizing plate with a thermoplastic resin film on one side, and the polarizer contained in the polarizing plate with a thermoplastic resin film on both sides obtained by the second lamination step or the polarizer separated therefrom also belong to the polarizer of the present invention.
[0175] The laminating step may further include a step of forming an adhesive layer on the side of the first thermoplastic resin film 102. As the adhesive constituting the adhesive layer, (meth) acrylic adhesives, styrene adhesives, silicone adhesives, rubber adhesives, urethane adhesives, polyester adhesives, epoxy copolymer adhesives, etc. can be used.
[0176] [Special Shape Processing]
[0177] The polarizing plate 100 can be obtained by cutting a long polarizing plate into single pieces, and then providing a concave portion at the outer edge of the single polarizing plate or providing a through hole in the surface. Alternatively, a concave portion can be provided at the outer edge of the polarizing plate and a through hole can be provided in the surface.
[0178] Specific examples of the method of providing a concave portion at the outer edge of a monolithic polarizing plate and the method of providing a through hole in the surface include, for example, a method of punching a monolithic polarizing plate using a Thomson knife to form an outer edge portion having a concave portion, a method of cutting the end surface of a monolithic polarizing plate using an engraving machine, a method of performing a perforation process using a rotary cutting tool such as a drill, etc. When performing special-shaped processing, the monolithic polarizing plate may be a single piece or a laminated body of multiple pieces stacked on top of each other.
[0179] <Image Display Device>
[0180] The polarizing plate can be used in an image display device. As the image display element used in the image display device, for example, a liquid crystal display element, an organic EL display element, etc. can be cited. When constructing a liquid crystal display device, the polarizing plate can be used as a polarizing plate arranged on the visible side, as a polarizing plate arranged on the backlight side, or as a polarizing plate on both the visible side and the backlight side. The polarizing plate can be attached to the image display device by means of an adhesive layer.
[0181] Example
[0182] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples. "%" and "parts" in the examples are mass % and mass parts unless otherwise specified. Tests and measurements were performed in the following manner.
[0183] [Determination of Contraction Force]
[0184] The polarizing plates obtained in the examples and comparative examples were cut into small pieces of 10 cm×5 cm, immersed in 600 mL of a solvent, and subjected to ultrasonic treatment at room temperature for 30 minutes to dissolve and remove the bonded thermoplastic resin film.
[0185] In addition, when both thermoplastic resin films on both sides of the polarizer were films formed of a polycycloolefin-based resin (COP film), cyclohexane was used as a solvent to perform dissolution and removal.
[0186] When both thermoplastic resin films on both sides of the polarizing plate are films formed of a triacetyl cellulose-based resin (TAC film), they are dissolved and removed using dichloromethane as a solvent.
[0187] When one thermoplastic resin film is a COP film and the other thermoplastic resin film is a TAC film, the TAC film is dissolved and removed using methylene chloride as a solvent, and then the COP film is dissolved and removed using cyclohexane as a solvent to dissolve and remove the thermoplastic resin film.
[0188] A sample for measuring MD shrinkage force with a width of 2 mm and a length of 10 mm, with the absorption axis direction (stretching direction) as the long side, was cut from the polarizing film after the thermoplastic resin film was removed. The sample was placed in a thermomechanical analyzer (TMA) "TMA7100" (manufactured by Hitachi High-Tech Science Co., Ltd.), and the shrinkage force in the long side direction (absorption axis direction, MD) generated when the sample was kept at a constant size at 80°C for 4 hours was measured.
[0189] [Heating test]
[0190] The polarizing plates obtained in the examples and comparative examples were bonded to the surface of alkali-free glass (Eagle XG manufactured by Corning Incorporated, 120×200×0.7 mm) after surface dirt was wiped off with ethanol, and then autoclaved at 50° C. This was used as an evaluation sample.
[0191] The evaluation sample was placed in a dry thermostatic bath at 85°C and heated for 250 hours. Thereafter, the sample was taken out of the bath and left to stand overnight (12 hours) at a temperature of 22°C and a humidity of 55%.
[0192] [Light leakage measurement]
[0193] like Fig. 9 As shown, a polarizing plate 202 that has not been subjected to a heating test is set on a backlight source 203, and a polarizing plate 201 of a sample subjected to a heating test is overlapped thereon. At this time, the polarizing plate 201 and the polarizing plate (unheated test) 202 are set in a manner of forming crossed nicols (in a manner of making the brightness the darkest). From above, a mask made of a black drawing paper cut out of the irregular shape of the polarizing plate 201 of the evaluation sample is matched with the irregular part of the polarizing plate 201 of the evaluation sample to cover it, thereby shielding the light directly radiated from the backlight source 203 without passing through the polarizing plate 201 and the polarizing plate (unheated test) 202, so that the leakage light is easily visible.
[0194] The illumination light from the backlight source 203 is 12000 cand / m 2 In this state, a camera (Nikon D5600) was used to shoot from 50cm directly above (fixed conditions: shutter speed 1s, aperture F5.6, ISO100, lens AF-P NIKKOR, zoom 18-55mm 55mm), and the degree of light leakage was compared.
[0195] In order to quantify the degree of light leakage for comparison, the light leakage degree L is determined according to the following procedure.
[0196] 1) The photograph of the sample for evaluation of the crossed Nicol prism state taken is read into a personal computer.
[0197] 2) Input the image into the image processing software (Microsoft Paint), and set the 8-bit RGB color value (0 to 255) of the part with the highest "brightness" value in the light leakage part of the outer edge of the polarizing plate as R E , G E , B E , the RGB values near the center of the polarizing plate where no light leaks in the plane are set as R C , G C , BC .
[0198] 3) At this time, the light leakage L is calculated according to the following formula.
[0199] L=〔(R E -R C ) 2 +(G E -G C ) 2 +(B E -B C ) 2 〕 1 / 2
[0200] [E=Edge(light leakage area), C=Center(central area)]
[0201] There is a tendency that the degree of light leakage becomes smaller as the L value becomes smaller.
[0202] [Measurement of water absorption of thermoplastic resin film]
[0203] The water absorption rate of the thermoplastic resin film used in each Example was measured by the following procedure.
[0204] The thermoplastic resin film was cut to prepare a sample film (about 50 mg).
[0205] The sample was placed in a dynamic vapor sorption analyzer "IGA Sorp" (manufactured by HIDEN ISOCHEMA, UK).
[0206] The mass of the sample film was measured while it was kept at 25°C dry condition. The mass after 24 hours was measured and used as the reference mass.
[0207] Next, the sample film was kept at 25°C and a relative humidity of 55% while measuring its mass. The mass after 6 hours was measured and taken as the mass after moisturizing.
[0208] The water absorption (%) was calculated according to the following formula.
[0209] Water absorption rate = (mass after moisturizing - base mass) / base mass × 100 (%)
[0210] [Production of polarizing plate]
[0211] The polarizing plate is manufactured by performing the following steps in sequence: 1) a preparation step, in which the polarizing plate is cut into sheet shapes and a portion of the samples are subjected to annealing treatment to reduce shrinkage; 2) a bonding step, in which the polarizing plate and the protective film are laminated via an adhesive and the adhesive is bonded (facing the image display panel); 3) a processing step, in which the polarizing plate sheet is punched into a special shape and the ends are ground.
[0212] 1. Preparation of polarizer
[0213] A polarizer (thickness 12 μm) with iodine adsorbed and oriented on a uniaxially stretched polyvinyl alcohol film (PVA) was prepared. A first substrate film (TAC film), a polarizer, and a second substrate film (PMMA film) were stacked in this order through a pure water layer, dried, and bonded to produce a laminated film. The first substrate film and the second substrate film can be easily peeled off. The laminated film was cut into a certain size (250 mm × 330 mm). At this time, the cutting was performed in a manner that the stretching direction of the polarizer was parallel to the long side direction or the short side direction of the cut sheet. Next, the second substrate film was gently peeled off from the end, and both sides were clamped with dust-free paper, and then clamped and fixed with an acrylic plate from the outside. Three groups were prepared, and they were left to stand or heated under the conditions of (1) temperature 85°C, drying (Dry), 12 hours, (2) temperature 85°C, drying (Dry), 3.5 hours, and (3) temperature 22°C, humidity 55%, and 1 night to obtain polarizers (1), (2) and (3). In (1) and (2), the mixture was heated and then allowed to stand overnight.
[0214] The contraction forces of the polarizers (1), (2) and (3) are 0.8N, 1.1N and 1.5N respectively.
[0215] 2. Fit
[0216] A film formed of a polycycloolefin resin (hereinafter also referred to as COP) and a film formed of a triacetyl cellulose resin (hereinafter also referred to as TAC) are cut into the same size as the polarizing plate (250×330 mm). The two thermoplastic resin films are bonded in such a way that the combination (thermoplastic resin film bonded to one side of the glass surface / thermoplastic resin film on the side opposite to the side bonded to the glass surface) becomes the following four structures: COP / COP (structure 1), COP / TAC (structure 2), TAC / COP (structure 3), TAC / TAC (structure 4). The TAC film uses a TAC film that has been saponified in advance. The bonding surface of each thermoplastic resin film is corona treated to improve the adhesion. The thermoplastic resin film on the side bonded to the glass surface is laminated with the polarizer side of the polarizer bonded with the first substrate film via a UV-curable adhesive, and UV light is irradiated from the first thermoplastic resin film side to cure the adhesive. Thereafter, the first base film bonded to the polarizing plate was gently peeled off from the edge, and a thermoplastic resin film on the side opposite to the side bonded to the glass surface was bonded to the surface in the same manner.
[0217] In addition, the water absorption rate of the COP film was 0.01%, and the water absorption rate of the TAC film was 2.01%.
[0218] The surface of the thermoplastic resin film on the side of the produced polarizing plate to be bonded to the glass surface was subjected to corona treatment, and an adhesive film was bonded thereto (facing the image display panel).
[0219] 3. Special-shaped processing
[0220] The completed polarizing plate sheet (250×330 mm) was punched out using a Thomson knife. Fig.10 The polarizing plates 300 shown in the figure were stacked to a thickness of about 10 mm. The stack of polarizing plates was clamped with PS (polystyrene) sheets punched into the same shape with a Thomson knife, and polished 300 μm from the ends with an engraving machine to obtain a Fig.10 Polarizing plate of the shape shown. The radius of curvature of the rounded corners 302, 303, and 304 are 5.0 mm, 6.0 mm, and 4.0 mm, respectively, and the corner 305 is a right angle. The concave portion 301 is 32.0 mm wide and 5.3 mm deep. The radius of curvature of the outer rounded corners 306, 307 and the inner rounded corners 308, 309 are 2.5 mm, 2.0 mm, 2.3 mm, and 2.5 mm, respectively. The concave portion 310 is 5.0 mm wide and 7.3 mm deep, the radius of curvature of the rounded corner 311 is 2.5 mm, the shortest distance 313 between the concave portion 301 and the center of gravity 312 of the polarizing plate is 64.7 mm, and the shortest distance 314 between the concave portion 310 and the center of gravity 312 of the polarizing plate is 62.7 mm.
[0221] <Examples and Comparative Examples>
[0222] The obtained polarizing plates were subjected to light leakage measurement after the heating test. The results of the concave portions 301 are shown in Table 1, and the results of the concave portions 310 are shown in Table 2, according to the configuration of each thermoplastic resin film.
[0223] [Table 1-1]
[0224]
[0225] [Table 1-2]
[0226]
[0227] [Table 1-3]
[0228]
[0229] [Table 1-4]
[0230]
[0231] [Table 2-1]
[0232]
[0233] [Table 2-2]
[0234]
[0235] [Table 2-3]
[0236]
[0237] [Table 2-4]
[0238]
[0239] From the results in Table 1 and Table 2, it can be seen that the polarizing plates according to the present invention all have low L values and light leakage is suppressed.
Claims
1. A polarizing plate comprising a polyvinyl alcohol-based resin polarizer and a first thermoplastic resin film provided on one surface of the polarizer, The water absorption rate of the first thermoplastic resin film is 0.1% or less, The polarizing plate has a concave portion at the outer edge portion or a through hole in the plane when viewed from above. The shrinkage force of the polyvinyl alcohol-based resin polarizer in the absorption axis direction per 2 mm width is 1.1 N or less. The shortest distance between the concave portion or the through hole and the center of gravity of the polarizing plate is 40 mm or more. The concave portion or the through hole is located in a region which is more than 20% of the area equivalent radius from the center of gravity of the polarizing plate.
2. The polarizing plate according to claim 1, wherein The polarizing plate has a concave portion at the outer edge portion in a plan view, The concave portion is a shape that is concave from the outer edge portion toward the inside when viewed from above, and the depth of the concave portion is greater than 0.1 mm. The outer corners of the concave portion are rounded, and the radius of curvature is 0.1 mm or more and 5 mm or less. The inner corner of the concave portion is rounded, and the radius of curvature is 0.1 mm or more and 5 mm or less, or The concave portion is a U-shaped concave portion in a plan view, and the depth of the concave portion is not less than 0.5 mm and not more than 10 mm. The curvature radius of the inner corner portion constituting the concave portion is greater than or equal to 0.5 mm and less than or equal to 10 mm.
3. The polarizing plate according to claim 1, wherein The first thermoplastic resin film is an acrylic resin film or a polycycloolefin resin film, ie, a COP resin film. 4 . The polarizing plate according to claim 1 , further comprising a second thermoplastic resin film provided on the other surface of the polyvinyl alcohol-based resin polarizer. 5 . 5 . A pressure-sensitive adhesive layer-attached polarizing plate comprising the polarizing plate according to claim 1 , and a pressure-sensitive adhesive layer provided on a first thermoplastic resin film side of the polarizing plate.
6. The polarizing plate with an adhesive layer according to claim 5, wherein The pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer for bonding the polarizing plate to an image display element. 7 . An image display device comprising the polarizing plate according to claim 1 .
8. A method for producing a polarizing plate, which is the method for producing a polarizing plate according to any one of claims 1 to 4, comprising: A preparation step of preparing a polyvinyl alcohol resin polarizer; A laminating step of laminating the polyvinyl alcohol-based resin polarizer to a first thermoplastic resin film; as well as The special-shaped processing step is to provide a concave portion at the outer edge of the polarizing plate or to provide a through hole in the surface. The preparation process includes an annealing process.
Citation Information
Patent Citations
Polarizing plate, optical film and image display device
JP2009098653A
Polarizing plate, method for producing polarizing film, and method for producing polarizing plate
JP2017182017A
Polarizing plate and manufacturing method thereof
TW201325895A
Polarizing film, polarizing plate, and method for manufacturing same
WO2018164176A1